Sistem Informasi Akuntansi Penjualan Produk Secara Kredit - Widiati, Wina; Rahardini, Ninda Islamiaty (Sistem Informasi Akuntansi Kampu Kabupaten Karawang, 2022)
Competition in the business world to make profits or sales according to the targets achieved. Sales of a company's source of income, a large increase in sales means a large increase in revenue earned by the company, to improve the performance of a company's sales system, it must run well because it becomes one of the important functions to develop the company. Regarding credit sales at PT. Hee Jung, West Java, the system used is still manual, starting from recording data and transactions using paper, so data damage or loss can occur and report generation is less efficient. The design of this system uses the Waterfall method as a software development method with an initial stage of software requirements analysis and the final stage, namely Support, this system has been analyzed regarding what is needed by users so that this system is useful for users and to create a transaction system so that data processing can be done. This is done to simplify the process of recording transactions, making reports easier and minimizing errors that occur.